Astrocyte, a Promising Target for Mood Disorder Interventions - Zhou, Xinyi; Xiao, Qian; Xie, Li; Yang, Fan; Wang, Liping; Tu, Jie (Frontiers in Molecular Neuroscience, 2019)
Mood disorders have multiple phenotypes and complex underlying biological mechanisms, and as such, there are no effective therapeutic strategies. A review of recent work on the role of astrocytes in mood disorders is thus warranted and we argue that there is tremendous potential for novel strategies for therapeutic interventions based on the role of astrocytes. Astrocytes are traditionally considered to have supporting roles within the brain, yet emerging evidence has shown that astrocytes have more direct roles in influencing brain function. Notably, evidence from postmortem human brain tissues has highlighted changes in glial cell morphology, density and astrocyte-related biomarkers and genes following mood disorders, indicating astrocyte involvement in mood disorders. Findings from animal models imply strongly that astrocytes not only change astrocyte morphology and physiological characteristics but also influence neural circuits via synapse structure and formation. This review pays particular attention to interactions between astrocytes and neurons and argues that astrocyte dysfunction affects the monoaminergic system, excitatory-inhibitory balance and neurotrophic states of local networks. Together, these studies provide a foundation of knowledge about the exact role of astrocytes in mood disorders. Changing focus from neurons to glial cells and their interactions is important so that we can understand newly proposed mechanisms underlying mood disorders, and to identify more diagnostic indicators or effective targets for treatment of these diseases.